The black cauldron - Alexander, Lloyd (New York : Bantam Doubleday Dell Books for Young Readers, 1990)
Taran, Assistant Pig-Keeper of Prydain, faces even more dangers as he seeks the magical Black Cauldron, the chief implement of the evil powers of Arawn, lord of the Land of Death.
"A Yearling book.".
Child Study Children's Book Committee.
Library Journal.
Newbery Medal/Honor.
Booklist, October 2007.
Child Study Children's Book Committee, August 2009.
Keywords: Fantasy; Good and evil -- Fiction; Prydain (Imaginary place) -- Fiction; Good and evil -- Fiction; Prydain (Imaginary place) -- Fiction; Fantastic fiction